Homes away from home : Jewish belonging in twentieth-century Paris, Berlin, and St. Petersburg - Wobick-Segev, Sarah (Stanford studies in Jewish history and culture., 2018)
This is a comparative study of Jewish communities in Western, Central, and Eastern Europe. It analyzes how Jews used social and religious spaces to reformulate patterns of fraternity, celebration, and family formation and expressions of self-identification. It suggests that the social patterns that developed between 1890 and the 1930s were formative for the fundamental reshaping of Jewish community and remain essential to our understanding of contemporary Jewish life